KEGIATAN PENINGKATAN KESADARAN PAJAK DAN PEMADANAN NIK-NPWP OLEH RELAWAN PAJAK UNIVERSITAS METHODIST INDONESIA - Goh, Thomas Sumarsan; Purba, Dimita H. P.; Rumapea, Melanthon; Simanjuntak, Arthur; Silalahi, Mulatua P.; Nainggolan, Arison; Purba, Sahala; Sembiring, Yosephine N. (Universitas Methodist Indonesia, 2023)
Tax volunteers are a government program, especially the Directorate General of Taxes, to increase tax inclusion in society. The Indonesian Methodist University recruited UMI students to become tax volunteer candidates, then conducted interviews and written tests. The Kanwil will inaugurate the tax volunteers who pass the selection. Tax volunteers this year apart from helping to increase tax awareness and assistance with filling out the SPT and reporting it, they also help socialize and assist in matching NIK-NPWP.